Bayesian Semi-Parametric Modeling of Infertility in Nigeria - Paul, Onatunji Adewale; Adedamola, Folorunso Serifat; A. O., Oluwasola Timothy; Ardo, Bamanga Muhammad; Aderemi, Folorunso Morufu (European Scientific Journal, ESJ, 2019)
Infertility in Nigeria is a neglected reproductive health issue despite its negative impact. Majority of infertility-related research has focused on treating the consequences of infertility rather than investigating the determinantsto explain the spatial and spline effect of infertility in the country. This work is aimed at investigating spatial variation of determinants of infertility among female in Nigeria. The finding reveals that women at reproductive age have a high probability of infertility in some southern part of Nigeria astheir ages are steadily increasing. Also, change in the characteristics of place of residence and source of water increase the chance of woman being infertile. Policy makers on health sectors should make effort to address problems of climatic and atmospheric change in the identified social and demographic risk factors.